I have been buried under years of dust : a memoir of autism and hope - Gilpeer, Valerie; Grodin, Emily, 1991- (William Morrow, an imprint of HarperCollinsPublishers, 2021)
A poet with nonverbal autism and her mother recount their shared 25-year struggle with unsuccessful therapies before an astonishing breakthrough led to a communication awakening and remarkable insights into the neurological science of the autism experience.